2013
DOI: 10.1105/tpc.113.112417
|View full text |Cite
|
Sign up to set email alerts
|

PIF4 and PIF5 Transcription Factors Link Blue Light and Auxin to Regulate the Phototropic Response in Arabidopsis

Abstract: Both blue light (BL) and auxin are essential for phototropism in Arabidopsis thaliana. However, the mechanisms by which light is molecularly linked to auxin during phototropism remain elusive. Here, we report that PHYTOCHROME INTERACTING FACTOR4 (PIF4) and PIF5 act downstream of the BL sensor PHOTOTROPIN1 (PHOT1) to negatively modulate phototropism in Arabidopsis. We also reveal that PIF4 and PIF5 negatively regulate auxin signaling. Furthermore, we demonstrate that PIF4 directly activates the expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 54 publications
3
124
2
Order By: Relevance
“…Overexpression of PIF4 doubles the expression level of YUC8 and elevates endogenous-free IAA levels to 50% above wild type (19). The expression of IAA29 was increased in a 35S-PIF4 overexpression line, and decreased in the pif4 pif5 double mutant compared with the wild type (20). In our experiments, PIF4 was up-regulated in the F1 hybrids and the three hybrid mimics and down-regulated in the small line (Sml-D) (Fig.…”
Section: Significancementioning
confidence: 57%
See 1 more Smart Citation
“…Overexpression of PIF4 doubles the expression level of YUC8 and elevates endogenous-free IAA levels to 50% above wild type (19). The expression of IAA29 was increased in a 35S-PIF4 overexpression line, and decreased in the pif4 pif5 double mutant compared with the wild type (20). In our experiments, PIF4 was up-regulated in the F1 hybrids and the three hybrid mimics and down-regulated in the small line (Sml-D) (Fig.…”
Section: Significancementioning
confidence: 57%
“…YUC8 and IAA29 are activated by the transcription factor PIF4 (19,20). The expression of the auxin biosynthesis genes TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS 1 (TAA1) and YUC8 can be induced by transzeatin treatment in wild-type plants, but not in a pif4 mutant, indicating PIF4 is required for cytokinin-dependent auxin biosynthesis, which leads to cell division (22).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, although PIFq members have been shown to inhibit seedling photomorphogenic development in blue light (Kang and Ni, 2006;Castillon et al, 2009;Kunihiro et al, 2010;Bu et al, 2011a), this effect appears to be mediated by phy, at least in the case of PIF1 and possibly PIF3 (Castillon et al, 2009;Bu et al, 2011a). By contrast, PIF4 and PIF5 have been shown to repress phototropism downstream of the blue light sensor phototropin (Sun et al, 2013).…”
Section: Pif Function In Phy-mediated Growth Responses To Light Phy Rmentioning
confidence: 92%
“…In turn, PIFs are also proposed to regulate auxin signaling by inducing the expression of several AUX/IAA and SAUR genes during deetiolation, shade, diurnal growth, and high-temperature responses (Franklin et al, 2011;Nozue et al, 2011;Hornitschek et al, 2012;Leivar et al, 2012b;Li et al, 2012). Interestingly, IAA19 and IAA29 (Sun et al, 2013), as well as SAUR19 (Franklin et al, 2011), are shown to participate in phototropic and high-temperature responses, respectively, downstream of the PIFs. During hook formation, PIFs regulate auxin transport by directly inducing WAG2 (Willige et al, 2012) and ethylene levels by directly inducing ACS5 and ACS8 expression Gallego-Bartolomé et al, 2011).…”
Section: Pifs As Systems Integrators Interface With Hormonal Pathwaysmentioning
confidence: 99%
“…PIF4 is a basic helix-loop-helix transcription factor that promotes hypocotyl elongation by activating the expression of genes involved in auxin biosynthesis, auxin signaling components, cell wall loosening, and cell expansion (Hornitschek et al 2012;Leivar and Quail 2011;de Lucas and Prat 2014;Sun et al 2013). Therefore, the up-regulation of PIF4 might lead to elevation of auxin biosynthesis and up-regulation of SAURs in ZTLoverexpressing seedlings.…”
mentioning
confidence: 99%